Comparison of bacterial diversity and abundance between sexes of Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae) from China - Guo, Chunhui; Peng, Xin; Zheng, Xialin; Wang, Xiaoyun; Wang, Ruirui; Huang, Zongyou; Yang, Zhende (PeerJ, 2020)
Background Insects harbor a myriad of microorganisms, many of which can affect the sex ratio and manipulate the reproduction of the host. Leptocybe invasa is an invasive pest that causes serious damage to eucalyptus plantations, and the thelytokous parthenogenesis, low temperature resistance, protection in galls, generation overlap and small body of L. invasa contribute to its rapid invasion and population growth. However, the endosymbiotic bacterial composition, abundance and sex differences of L. invasa remain unclear. Therefore, this research aimed to identify the bacterial communities in L. invasa adults and compare them between the sexes of L. invasa lineage B. Results The Illumina MiSeq platform was used to compare bacterial community composition between females and males of L. invasa by sequencing the V3–V4 region of the 16S ribosomal RNA gene. A total of 1,320 operational taxonomic units (OTUs) were obtained. These OTUs were subdivided into 24 phyla, 71 classes, 130 orders, 245 families and 501 genera. At the genus level, the dominant bacteria in females and males were Rickettsia and Rhizobium, respectively. Conclusion The endosymbiotic bacteria of L. invasa females and males were highly diverse. There were differences in the bacterial community of L. invasa between sexes, and the bacterial diversity in male specimens was greater than that in female specimens. This study presents a comprehensive comparison of bacterial communities in L. invasa and these data will provide an overall view of the bacterial community in both sexes of L. invasa with special attention on sex-related bacteria.
Keywords: Leptocybe invasa; 16S rRNA; High throughput sequencing; Bacteria; Diversity